Coupling All-Atom Molecular Dynamics Simulations of Ions In Water With Brownian Dynamics - BOGA, SRINIVAS; BANDARI, NARENDRA; THOTI, NARESH; THOTI, NARESH (International Journal of Psychosocial Rehabilitation, 2025)
Investigations are conducted using molecular dynamics (MD) simulations of ions (K+, Na+, Ca2+, and Cl−) in aqueous solutions. We use the SPC/E model to explain water. Using MD simulations, a stochastic coarse-grained description of ion behavior is presented and parameterized. It describes the position, acceleration, and velocity of the ions and is presented as a system of coupled stochastic and ordinary differential equations. A description in between Brownian dynamics (BD) models and all-atom MD simulations is offered by the stochastic coarse-grained model. It is applied to the development of a multiscale technique that employs (less detailed) BD simulations in the remaining computational region and all-atom MD simulations in other areas.